Faith, Belief and Fictionalism. (5th August 2016) - Malcolm, Finlay; Scott, Michael
Abstract: Is propositional religious faith constituted by belief? Recent debate has focussed on whether faith may be constituted by a positive non‐doxastic cognitive state, which can stand in place of belief. This article sets out and defends the doxastic theory. We consider and reject three arguments commonly used in favour of non‐doxastic theories of faith: (1) the argument from religious doubt; (2) the use of 'faith' in linguistic utterances; and (3) the possibility of pragmatic faith. We argue that belief is required to maintain a distinction between genuine faith, pretend faith, and fictionalist faith.